Bioavailability of phosphorus to loblolly pine and red maple in clay and saprolite from the southeastern Piedmont, USA. Issue 6 (22nd September 2022) - Wang, Zhine; Thompson, Aaron; Sutter, Lori; Markewitz, Daniel
Abstract: Soil P is present in multiple forms through the profile with plants potentially accessing different P pools at different depths through distinct pathways. Understanding P pool distribution and dynamics is necessary for sustainable forest management. Our research investigates soil P dynamics in clay (at 60–100 cm depth) and saprolite (at 450–500 cm depth) of the Calhoun Critical Zone Observatory (CCZO) in South Carolina through a 1‐yr greenhouse planting of loblolly pine ( Pinus taeda L.) and red maple ( Acer rubrum L.). We compared total plant P uptake to changes in soil P pools defined by Mehlich 3 (MIII) P, Hedley P, or total P fractions and to indices of potential iron (Fe) reduction and phosphatase activity as potential pathways of P release. We hypothesized that (a) the soil content of MIII P would be insufficient to meet plant demand; (b) ectomycorrhizal (EM) pine to differ from arbuscular mycorrhizal (AM) maple in accessing organic P pools; and (c) Fe reduction to correlate with declines in NaOH P (associated with Fe‐bound P) with greater decreases in the Fe‐oxide‐rich clay layer. Our results indicated MIII extractable P is plant available but present in insufficient quantities to meet total demand. In Hedley P pools, resin Pi and NaOH Pi supplied the most P for plant growth, and stable P pools (concentrated HCl P and residual P) buffered losses from these P pools. Plant‐available P in these soils seems sufficient to meet long‐term plant demand particularly if deeply rooted trees grow into the saprolite that had higher available soil P supply. Core Ideas: Saprolite was richer than clay in MIII P and total P. Resin Pi and NaOH Pi were dynamic pools that contributed to plant growth. Residual P and con HCl Pi decline indicated stable P pools replenish the loss of labile P. No clear evidence that plants facilitate soil iron reduction. Ectomycorrhizal plants didn't produce more phosphatase than arbuscular plants in the short‐term.